IMPLEMENTASI KEBIJAKAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP): (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lombok Utara) - Khanti Citta Anuttari (Jurnal Administrasi Publik, 2024)
Implementation of Electronic Identity Card (E-KTP) Policy (Study at the Population and Civil Registration Service of North Lombok Regency). Normatively, population administration is implemented by the Population and Civil Registration Service assisted by employees who are competent in their fields. Through this, the research results were found: (1) The implementation of the e-KTP policy was carried out quite well, there was a lack of human resources and a lack of budget. In fact, when linked to the Law regulating Population Administration, resources are an important aspect in the success of the implementation process. (2) Obstacles in implementing the e-KTP policy, researchers found that there were budget limitations, staff limitations, lack of awareness from the community, and geographical location. (3) The results of the implementation of the e-KTP policy, if implemented well, have an impact resulting from the e-KTP policy, such as efficiency in population administration and social and economic impacts. The efficiency of population administration results in the process of making e-KTP becoming faster. The resulting social impact is that underprivileged communities that are integrated with e-KTP can receive social assistance from the government. The economic impact is a society integrated in e-KTP data. Economically, the use of e-KTP aims to facilitate economic activities such as opening a bank account.